Anomalies of the first sharp diffraction peak in network glasses: Evidence for correlations with dynamic and rigidity properties. Issue 5 (18th February 2013) - Micoulaut, Matthieu; Bauchy, Mathieu
Abstract <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> The structural and dynamical properties of densified sodium silicates are investigated using molecular dynamics (MD) simulations. From the analysis of the first sharp diffraction peak (FSDP) in the amorphous phase, it is shown that some of its characteristic parameters (position, width) in partial structure factors display minima in a certain pressure interval defining a window. The pressure window can be correlated with anomalies in transport properties (diffusion, viscosity) and their activation barriers. The count of topological constraints, sensitive to pressure and temperature, is also computed. In the pressure window, we find evidence that an adaptative behavior takes place as angular constraints soften and reduce the increasing network connectivity related strain induced by pressure. These findings display striking similarities with the Boolchand intermediate phase (IP) found in rigidity driven by composition. The present numerical results also suggest that structural signatures for the IP should be found from a detailed analysis of neutron structure factors involving the partials. Finally, on a more general ground, the present study links for the first time to the best of our knowledge characteristic features of the FSDP with transport properties in the liquid.